Reduced graphene oxide with controllably intimate bifunctionality for the catalytic transformation of fructose into 2,5-diformylfuran in biphasic solvent systems - Chen, Z. (2021)
For responding to the rapidly increasing trend of research on biorefinery, a diverse range of furans derived from biomass emerge as versatile platform chemicals for a spectrum of pharmaceutical applications. However, it is a formidable challenge to transform biomass feedstock into valuable furan-based chemicals via complicated cascade reactions. Here, we develop a bifunctional reduced graphene oxide (rGO)-supported catalyst with two controllably intimate active sites (namely Ru species and sulfonic acid groups, respectively) on the graphene sheets. The structural and morphological evolution of the catalyst is characterized by FTIR, Raman, XPS, XRD, SEM, and HR-TEM. This catalyst is employed in a biphasic solvent system for the one-pot conversion of fructose to 2,5-diformyfuran (DFF) which is a high-value pharmaceutical intermediate. We demonstrate that the nanoscale proximity of two active sites and the solvent composition are crucial to the catalytic activity and DFF selectivity in the cascade catalysis. The spatial organization of Ru species and sulfonic acid groups reveals an optimized inter-site distance of 12.5 ± 2.2 nm for the high catalytic activity. A solvent-influenced kinetic model is established and accurately elaborates the regulatory role of toluene (as the co-solvent) on the reaction pathways. More importantly, this bifunctional catalyst can be recycled for 4 times without significant loss of catalytic activity. Taken together, a deep understanding is highlighted which provides clues on the optimization of multifunctional catalysts and the choice of solvent system in the cascade catalysis which is a general unit operation in chemical engineering processes.